Neil McKinnon interviewed by Roslyn Flood in the Cultural context of unemployment oral history project - McKinnon, Neil.; Flood, Roslyn; Cultural Context of Unemployment Project. Brisbane Team. (1985)
McKinnon speaks of his background; work experience; education; being retrenched at age 52 and how he coped; feelings and emotions; community reactions; changes to his lifestyle; looking for work; finances; age and work; unemployment; the modern workforce; the need for career training; working in a country town.
Recorded by the Brisbane Team (Rural) of the Cultural Context of Unemployment Project, a CEP program administered by the National Library of Australia.
Digital master available
Transcript available (30 p.)
Keywords: McKinnon, Neil -- Interviews; Unemployment -- Social aspects -- Queensland -- Warwick; Unemployed -- Queensland -- Case studies; Age and employment -- Queensland